Assessment of Bacteriological Quality of Sheep Carcasses, Effect Level of 2.5% Citric Acid Spray on Bacterial Contamination of Meat, and Hygiene Practices of Workers in a Selected Abattoir in Debrezeit Town, Central Ethiopia - Derebew Aynewa; Zemichael Gizaw; Aklilu Feleke Haile (SAGE Publishing, 2021)
Background: Meat safety is important for public health. As part of the meat chain abattoirs are required to give attention to meat hygiene and safety in order to minimize hazards. Therefore, the current study was conducted to evaluate the bacteriological quality of sheep carcasses, knowledge and hygienic practices of workers in a selected abattoir and to determine the effect level of 2.5% citric acid spray on total coliforms and aerobic bacteria load of raw sheep carcasses surfaces. Methods: A cross-sectional study design with structured questionnaire and observational checklists observation were used. A systematic random sampling technique was employed. A total of 50 sample swabs (25 swabs before citric acid spray and 25 after citric acid spray) were randomly taken from brisket, flank and rump of sheep's carcasses. Swabs were moistened with buffered peptone water (BPW) and samples were taken by rubbing 100 cm 2 (10 cm × 10 cm) area delineated by sterile aluminum template. In addition, we administered a structured questionnaire and an observational checklists to assess knowledge and hygienic practices of workers. Bacteriological quality of sheep carcasses were analyzed using the methods described by the US bacteriological analytical manual. Results: The mean count for aerobic bacteria of the sheep carcasses before and after citric acid spray were 7.2log 10 CFU/ml and 6.4log 10 CFU/ml, respectively. The test results also showed that 21 (84%) and 15 (60%) of the swab samples were positive before and after spraying citric acid, respectively. The mean counts for coliform bacterial of the sheep carcasses before and after citric acid spray were 3.5log 10 CFU/ml and 2.9log 10 CFU/ml, respectively. The mean total aerobic and coliform counts before and after citric acid spray were significantly different ( P  < .05). Regarding the hygiene condition of workers, all the respondents reported that they always washed their hands with soap before and after entering the slaughtering room and 23 (53.5%) of the workers reported that they used hot water. Thirty-one (72.1%) of the workers reported that they do not used soap to wash hands after visiting toilet. Thirty-five (81.4%) of the production workers did not wear mouth mask while handling and distribute meat/carcass. On the other hand, all of the workers wore capes, gowns and boots at the time of the observation and only 18 (18.6%) of the production workers wore gloves at the time of the survey. Conclusion: The current study revealed that significant proportion of sheep carcasses were positive for t otal aerobic bacteria and total coliform. Moreover, the study also showed that spraying of sheep carcasses with 2.5% citric acid significantly reduced the total coliform and aerobic counts. However, we did not assessed how much spray results to this effect. Therefore, we recommended further studies to determine how much spray of 2.5% citric acid significantly reduce bacterial contamination of sheep carcasses. In addition, the abattoir has to follow the food hazard analysis critical control point (HACCP) system to minimize meat contamination during harvesting and processing. The abattoir has to also implement strict operation laws to improve hygiene conditions of the workers. In addition, the abattoir can minimize meat contamination using 2.5% citric acid as a decontaminant.